'. . . and then no more kisses!' Exploring patients' experiences on multidrug-resistant bacterial microorganisms and hygiene measures in end-of-life care A mixed-methods study. (February 2020) - Heckel, Maria; Sturm, Alexander; Stiel, Stephanie; Ostgathe, Christoph; Herbst, Franziska A; Tiedtke, Johanna; Adelhardt, Thomas; Reichert, Karen; Sieber, Cornel
Background: In end-of-life care hygiene, measures concerning multidrug-resistant bacterial microorganisms may contradict the palliative care approach of social inclusion and be burdensome for patients. Objectives: To integrate patients' perspectives on handling multidrug-resistant bacterial microorganisms at their end of life, their quality of life, the impact of positive multidrug-resistant bacterial microorganisms' diagnosis, protection and isolation measures on their well-being and patients' wishes and needs regarding their care. Design: A mixed-methods convergent parallel design embedded quantitative data on the patients' multidrug-resistant bacterial microorganisms' trajectory and quality of life assessed by the Schedule for the Evaluation of Individual Quality of Life in qualitative data collection via interviews and focus groups. Data analysis was performed according to Grounded Theory and qualitative and quantitative results were interrelated. Setting/participants: Between March 2014 and September 2015 at two hospitals adult patients diagnosed with multidrug-resistant bacterial microorganisms and treated in a palliative care department or a geriatric ward were included in the sample group. Results: Patients in end-of-life and geriatric care reported emotional and social impact through multidrug-resistant bacterial microorganisms' diagnosis itself, hygiene measures and lack of information. This impact affects aspects relevant to the patients' quality of life. Patients' wishes for comprehensive communication/information and reduction of social strain were identified from the focus group discussion. Conclusion: Patients would benefit from comprehensible information on multidrug-resistant bacterial microorganisms. Strategies minimizing social exclusion and emotional impact of multidrug-resistant bacterial microorganisms' diagnosis in end-of-life care are needed as well as adaption or supplementation of standard multidrug-resistant bacterial microorganisms' policies of hospitals.